2017
DOI: 10.14712/18059694.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fibromyalgia Syndrome and Its Correlations with Arrhythmia in Patients with Palpitations

Abstract: FMS frequency and HAD anxiety scores were found to be higher in patients with palpitation complaints. However, we found no association between arrhythmia, EPS parameters and FMS. In our clinical practice we should keep in mind to carry out assessments in terms of FMS in patients with palpitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…P. Acosta et al identified an increased probability of cardiovascular diseases among fibromyalgia patients, especially in females who did not meet physical strength criteria (15). Askin et al reported a higher prevalence of FM symptoms among cardiac patients using the Fibromyalgia Impact Questionnaire and VAS scale for pain, finding 22 symptoms in 62 patients versus 4 in normal subjects (16). Y. Muskila's study on gender differences in FM incidence included 321 individuals and reported a higher incidence in women (11.4%) compared to men (1.5%) (17).…”
Section: Discussionmentioning
confidence: 99%
“…P. Acosta et al identified an increased probability of cardiovascular diseases among fibromyalgia patients, especially in females who did not meet physical strength criteria (15). Askin et al reported a higher prevalence of FM symptoms among cardiac patients using the Fibromyalgia Impact Questionnaire and VAS scale for pain, finding 22 symptoms in 62 patients versus 4 in normal subjects (16). Y. Muskila's study on gender differences in FM incidence included 321 individuals and reported a higher incidence in women (11.4%) compared to men (1.5%) (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some of the sensory non-pain related symptoms highlighted in the current study, such as tinnitus, palpitations, vertigo, nausea are also due to central augmentation but have received less attention in the literature. For example, some studies have shown a mismatch between self-reporting of palpitations amongst patients with fibromyalgia, compared to healthy controls, in the absence of any significant differences in objective cardiac measurements [7,20]. Autonomic dysfunction has also been proposed as a potential mechanism for some for the symptoms identified by the SMP including palpitations and skin manifestations, but objective data to support this 10/22 theory is currently lacking [7,27,44].…”
Section: Fibromyalgiamentioning
confidence: 99%
“…For example, some studies have shown a mismatch between self-reporting of palpitations amongst patients with fibromyalgia, compared to healthy controls, in the absence of any significant differences in objective cardiac measurements [7,20]. Autonomic dysfunction has also been proposed as a potential mechanism for some for the symptoms identified by the SMP including palpitations and skin manifestations, but objective data to support this 10/22 theory is currently lacking [7,27,44]. Diminished concentration is a well-established phenotype of fibromyalgia, and was incorrectly marked as 'not established' during the validation phase.…”
Section: Fibromyalgiamentioning
confidence: 99%